The response of semi‐arid ephemeral wetland plants to flooding: linking water use to hydrological processes. Issue 5 (18th September 2012) - Drake, Paul L.; Coleman, Blaire F.; Vogwill, Ryan
ABSTRACT Evergreen plants inhabiting ephemeral wetlands endure long dry spells interspersed with periods of flooding (or inundation). Inundation events are likely to be important for plant water use and growth, but few studies have linked the physiology of plants to hydrological processes during flood. We investigated the link between changes in the soil physical environment and plant water use traits in a stand of Casuarina obesa Miq and Melaleuca strobophylla Barlow trees during a controlled inundation event at Toolibin Lake. Toolibin Lake is an internationally recognized ephemeral wetland, which is under threat from altered hydrology and salinization. During flood, the velocity of water movement through the clay‐dominated soil profile suggested that macropores and plant root preferential flow paths aided water distribution. C. obesa was more capable than M. strobophylla to capitalize on the inundation event, suggesting preferential use of macropore water and a concentration of roots near the soil surface. Sap flux (QS) and tree diameter (ϕ) were interdependent and there was a correlation between increasing ϕ and increasing pre‐dawn leaf water potential (Ψpd). These observations link the movement of water through the soil profile with changes in tree water use and tree girth in C. obesa and M. strobophylla. Changes in the soil physical environment observed in this study also highlight the risks associated with hydrological management in salinity‐affected ecosystems. Although floods provide fresh water to the root zone of trees, the resulting recharge may also elevate saline groundwater into the region of plant water uptake. Copyright © 2012 Commonwealth of Australia